IMPLIKASI HUKUM PENGENDALIAN DAMPAK LINGKUNGAN DALAM PEMBANGUNAN PERUMAHAN DI KABUPATEN KARIMUN - Cendy Glaksy; Lu Sudirman; Junimart Girsang (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The construction of housing and settlements in urban areas generally takes place rapidly, requiring large areas of land. The construction of housing and settlements is one of the fundamental problems faced by the government, including in Karimun Regency. This study examines the legal implications of controlling environmental impacts in housing development in Karimun district, policies related to environmental law, urban spatial planning. This research is a normative legal research based on the results of library research. The secondary data are in the form of laws and regulations in the field of environmental law, urban spatial planning, land law, books and research results in the field of environmental law. Sustainable development and controlled use of natural resources are the objectives of environmental management. To achieve the goal, it must be estimated changes in environmental conditions, both favorable and unfavorable.